a, the AN ANALYSIS OF SLANG USED IN THE MOVIE GUNS AKIMBO BY JASON LEI HOWDEN - EKA, NI WAYAN EKAYANTI (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2023)
Slang is a confidential, informal and characteristic of spoken language which is created and used by a particular community. This study discusses about slang words in Guns Akimbo movie. This study aims to find out the types of slang and functions of slang used in the Guns Akimbo movie. In this study the researcher used the theory of Allan and Burridge (2006) in identifying the types of slang and the theory of Hymes (1998) in identifying the function of slang. The source of the data was taken from the script of Guns Akimbo movie. The result of this study showed that there were 5 types of slang used in the Guns Akimbo movie. They were fresh and creative, flippant, imitative, acronym and clipping. The type of fresh and creative dominates the type of slang words used in the Guns Akimbo movie. While regarding the functions of slang, it was found 7 functions of slang in this movie. They were to address, to humiliate, to initiate relax conversation, to form intimate atmosphere, to express impression, to reveal anger and to show intimacy. The function of slang which has the highest frequency discovered in this movie is to revel anger. In conclusion, slang is a common word used in spoken language. We need to understand them in order not to get misunderstanding.